Pengaruh Enterprise Risk Management, Corporate Social Responsibility, Free Cash Flow dan Leverage Terhadap Nilai Perusahaan pada Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019 - Namira Ufrida Rahmi; Venny Veronika Wijaya (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to examine the effect of Enterprise Risk Management, Corporate Social Responsibility, Free Cash Flow and Leverage on Firm Value in consumer goods industry sector companies listed on the Indonesia Stock Exchange n 2016-2019 period. Firm value shows that the value of all assets owned by company, which can be used as a sign for investors to invest in a company. This research used a method with a quantitative descriptive approach. The population in this study were the consumer goods companies listed in Indonesia Stock Exchange (IDX) during the period 2016 to 2019 with a total of 40 companies and the sampling technique used purposive sampling and obtained 24 companies in consumer goods sector. Data analysis used multiple linear regression analysis, classical assumption test, the coefficient of determination test, F test and t test. The results of the study show that partially corporate social responsibility and free cash flow have significant effect on the firm value but enterprise risk management and leverage have no effect on the firm value. Variable enterprise risk management, corporate social responsibililty, free cash flow and leverage simultaneously have a significant effect on firm value in consumer goods industry sector listed on Indonesia Stock Exchange in 2016-2019.